Cationic Surfactant-Induced Instantaneous Gelation of Silk Fibroin Solution - Lu, Shenzhou; Sun, Shan; Zhang, Fang; Li, Jiaojiao; Xing, Tieling; Jin, Jian (Asian Journal of Chemistry, 2014)
Modern traumatic wound-care products have several associated disadvantages. They do not meet requirements because they lack good permeability, biocompatibility and air tightness. In an attempt to overcome these shortcomings, a new type of flexible, instantaneously-formed hydrogels resulting from blending silk fibroin and cationic surfactants with different carbon chains are introduced in this work. The secondary structure of these hydrogels is similar to that of a silk fibroin solution as they primarily consist of random coils. However, the structure is different from a pure silk fibroin hydrogel which primarily consists of b-sheet structure. By means of SEM, silk fibroin molecules form clustered nanofilaments during the cationic surfactant-induced hydrogelation, which is different from a pure silk fibroin hydrogel that is composed of a porous network structure. The charge effect, hydrophobic effect and surface tension are presumed to be related to the formation of the cationic surfactant/silk fibroin hydrogels.